ASSESSMENT OF ICT COMPETENCIES POSSESSED BY NCE GRADUATE BUSINESS STUDIES TEACHERS IN ENUGU STATE. (NAU Journal of Technology and Vocational Education, 2024)
The study was undertaken to determine the level of ICT competencies of Businessstudies teachers in junior secondary schools in Enugu East senatorial zone of Enugu stateNigeria. Two research questions guided the study and two null hypothesis were tested.Survey design was adopted and the population consisted of 352 NCE graduate teachers injunior secondary schools in the area. The entire population was used for the study. Theinstrument used was questionnaire with a 5 point rating scale containing 27 items in twosections. The instrument was validated by three experts, two in measurement andevaluation and one in computer science. The reliability of the instrument was determinedusing cronbach Alpha reliability formula forinternal consistency and reliability. Coefficientsof 0.76 and 0.85 were obtained for the two sections. Data in respect of a researchquestions were analysed using mean and standard deviation while the hypotheses weretested using independent t-test (I tail, p-val = 0.05) on SPSS software. The two researchquestions showed that the ICT competency of teachers were moderate. All the twohypotheses tested showed that there were significant differences between the meanresponses of the teachers (mean = 0.05), hence all the null hypotheses were rejected. Thestudy revealed that teachers were not highly competent in ICT to enhance theirteachings. Based on the finding of the study, it was recommended that governmentshould organise workshops, seminars and conferences for secondary school teachers toenhance their ICT competencies and also grant study leave with pay to teachersto enablethemembarkonICTtraining programmes.